2016
DOI: 10.1097/md.0000000000002936
|View full text |Cite
|
Sign up to set email alerts
|

dCK Expression and Gene Polymorphism With Gemcitabine Chemosensitivity in Patients With Pancreatic Ductal Adenocarcinoma

Abstract: The aim of this study was to investigate the relationship of deoxycytidine kinase (dCK) protein expression and gene single-nucleotide polymorphisms to gemcitabine chemosensitivity in patients with pancreatic ductal adenocarcinoma (PDAC).In total, 54 patients with resectable PDAC, who received postoperative gemcitabine-based therapy, were enrolled in this study, from January 2011 to April 2013. The dCK protein expression was measured retrospectively by immunohistochemistry. Furthermore, 5 single-nucleotide poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…32 In line with the essential roles of hENT1 and dCK in gemcitabine metabolism, the hENT1 knockdown in biliary tract cancer cells 20 and dCK knockdown in pancreatic cancer cells 19 attenuated cell sensitivity to gemcitabine, which is consistent with the present results. High expression levels of hENT1 or dCK were associated with better survival in gemcitabine-treated cholangiocarcinoma 20 , 21 and pancreatic cancer, 17 , 18 , 22 , 23 indicating that the functional roles of hENT1 and dCK in vitro reflect their roles in gemcitabine sensitivity in clinical settings. Therefore, the present results demonstrated that patients with meningiomas expressing high levels of hENT1 and dCK may benefit from gemcitabine-based chemotherapy and, thus, clinical trials to test the efficacy of gemcitabine in high-grade meningiomas are warranted.…”
Section: Discussionmentioning
confidence: 98%
“…32 In line with the essential roles of hENT1 and dCK in gemcitabine metabolism, the hENT1 knockdown in biliary tract cancer cells 20 and dCK knockdown in pancreatic cancer cells 19 attenuated cell sensitivity to gemcitabine, which is consistent with the present results. High expression levels of hENT1 or dCK were associated with better survival in gemcitabine-treated cholangiocarcinoma 20 , 21 and pancreatic cancer, 17 , 18 , 22 , 23 indicating that the functional roles of hENT1 and dCK in vitro reflect their roles in gemcitabine sensitivity in clinical settings. Therefore, the present results demonstrated that patients with meningiomas expressing high levels of hENT1 and dCK may benefit from gemcitabine-based chemotherapy and, thus, clinical trials to test the efficacy of gemcitabine in high-grade meningiomas are warranted.…”
Section: Discussionmentioning
confidence: 98%
“…The pharmacological activity of these nucleoside analogs is dependent on phosphorylation by DCK [ 20 ]. The expression of the dCK gene and protein and single-nucleotide SNPs in the dCK gene have been closely associated with gemcitabine chemosensitivity in patients with pancreatic cancer [ 21 23 ]. By employing immunohistochemistry, a small retrospective study found that high levels of dCK protein expression correlated positively with OS in pancreatic cancer patients undergoing adjuvant gemcitabine chemotherapy [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Sixty to seventy percent of newly diagnosed pancreatic cancer patients present with advanced disease. The 5-year survival among these patients is only 5% to 7%, [ 3 , 4 ] and the vast majority of patients survive less than 1 to 2 years. Even following curative surgery, 90% of patients progress in 12 to 18 months.…”
Section: Introductionmentioning
confidence: 99%